In Vivo Activity of Gonadotropin Releasing Hormone (cGnRH-II, sGnRHa and LHRHa) in African Catfish, (Clarias Gariepinus B.) and Javanese Barb, (Barbodes Gonionotus B.) - Mohd Taufek, Norhidayah (2010)
Gonadotropin hormone releasing hormone (GnRH) is a peptide hormone that is responsible for stimulating the release of gonadotropins from pituitary and consequently influence the steroid hormone production level in the ovary. Six experiments have been conducted to determine the effectiveness of cGnRH-II as an inducing agent for maturation and ovulation in Clarias gariepinus and Barbodes gonionotus. The first experiment determined the effectiveness of native cGnRH-II when compared with analog LHRHa, and sGnRHa with saline used as control. The concentration of all the hormones used in this experiment was 20μg/kg. For the second experiment, three different concentrations were given; 2 μg/kg, 20 μg/kg and 200 μg/kg with saline as a control. Finally, the third experiment examined the pimozide (PIM) as dopamine inhibitor with the combination of cGnRH-II to accelerate the maturation and ovulation. The hormones involved were cGnRH-II 200 μg/kg; 5mg/kg PIM; cGnRH-II 200 μg/kg + 5mg/kg PIM and saline. All the hormones were administered as a single injection. The experimental parameters observed were hormonal changes in the fishes and Germinal Vesicle (GV) movement during the experiment. Each group consisted of six sexually mature females ranging from 450-550 g Body Weight (BW). The GV was examined prior to injection at 0h, 6h, 12h and 24h post injection and ranked from 1 (GV at central location) to 4 (at ovulation stage). Blood were sampled at the same time as the GV examination. Plasma sample were analyzed for Testosterone (T) and 17ß-Estradiol (E2) concentrations using Enzyme Link Immunosorbent assay (ELISA). Hatching and fertilization rates were determined and data for plasma steroid hormones and the GV were analyzed using analysis of variance (ANOVA). For African catfish, sGnRHa showed the most outstanding effect compared to the two treatments (LHRHa and cGnRH-II) since it is more resistance to degradation when compared with native peptides. The 200μg/kg cGnRH–II proved to be effective in stimulating maturation and ovulation. Saline injected fish remained unchanged where the initial GV was at stage 1.00±0.00. The cGnRH-II alone was enough to induce maturation and ovulation in African catfish. All fish ovulated in both groups (cGnRH-II alone and cGnRH-II + PIM) while the GV showed significant migration throughout the experiment (P<0.05). Fertilization rate constituted 73% and 80% while hatching rates were 58% and 67% for cGnRH-II alFor Javanese barb, sGnRHa was more potent compared to the cGnRH-II and LHRHa. In the graded dosage experiment, 200 μg/kg cGnRH-II seemed to induce for oocyte maturation but no ovulation occurred. However, addition of Pimozide increase the plasma steroid level compared to cGnRH-II alone. The plasma steroid hormone for the saline treated group in all the experiment remained the same throughout the study (P>0.05). Although no ovulation was observed, the plasma steroid hormones and GV of cGnRH-II treated group showed significant effect compared to saline group (P<0.05). The cGnRH-II was proven to effectively induced maturation and ovulation in both the Javanese barb and African catfish although large number of dosage was required. The use of a potent cGnRH-II analog for the improvement of spawning induction therapies is strongly suggested to increase the performance of cGnRH-II.one and cGnRH-II + PIM treatments, respectively. For Javanese barb, sGnRHa was more potent compared to the cGnRH-II and LHRHa. In the graded dosage experiment, 200 μg/kg cGnRH-II seemed to induce for oocyte maturation but no ovulation occurred. However, addition of Pimozide increase the plasma steroid level compared to cGnRH-II alone. The plasma steroid hormone for the saline treated group in all the experiment remained the same throughout the study (P>0.05). Although no ovulation was observed, the plasma steroid hormones and GV of cGnRH-II treated group showed significant effect compared to saline group (P<0.05). The cGnRH-II was proven to effectively induced maturation and ovulation in both the Javanese barb and African catfish although large number of dosage was required. The use of a potent cGnRH-II analog for the improvement of spawning induction therapies is strongly suggested to increase the performance of cGnRH-II.